2019
DOI: 10.5230/jgc.2019.19.e39
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers for Prediction of Response to Preoperative Systemic Therapies in Gastric Cancer

Abstract: Preoperative chemo- and radiotherapeutic strategies followed by surgery are currently a standard approach for treating locally advanced gastric and esophagogastric junction cancer in Western countries. However, in a large number of cases, the tumor is extremely resistant to these treatments and the patients are exposed to unnecessary toxicity and delayed surgical therapy. The current clinical trials evaluating the combination of preoperative systemic therapies with modern targeted and immunotherapeutic agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
0
11
0
1
Order By: Relevance
“…It was reported that the expression level of HOXB9 was a potential prognostic factor for LUAD since the upregulated HOXB9 was correlated with the advanced clinicopathological staging (28). Recent studies showed that HOXB9 was a critical transcription factor for the drug resistance of tumors, the expression silence of which would be very promising for ameliorating the resistance of tumor cells to the agent (29). However, some studies proposed a thoroughly opposite view, concluding that the downregulation of HOXB9 was correlated with the poor survival prognosis of patients bearing adenocarcinoma of the colon, ductal adenocarcinoma of the pancreas, and gastric carcinoma (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression level of HOXB9 was a potential prognostic factor for LUAD since the upregulated HOXB9 was correlated with the advanced clinicopathological staging (28). Recent studies showed that HOXB9 was a critical transcription factor for the drug resistance of tumors, the expression silence of which would be very promising for ameliorating the resistance of tumor cells to the agent (29). However, some studies proposed a thoroughly opposite view, concluding that the downregulation of HOXB9 was correlated with the poor survival prognosis of patients bearing adenocarcinoma of the colon, ductal adenocarcinoma of the pancreas, and gastric carcinoma (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…This classification has provided a significant understanding of the molecular and heterogeneous profiles of gastric cancer across different demographics. In addition to genetic changes such as Her2neu amplification, fibroblast receptor amplification/mutation, gross factor fibroblast receptor amplification/mutation, PDL 1/PD1 pathway amplification were listed 20 , 26 . These factors have been used as prognostic as well as treatment factors.…”
Section: Discussionmentioning
confidence: 99%
“…After a certain period of trastuzumab treatment, almost all patients will develop drug resistance even if the primary resistance is very rare in patients in HER2 overexpression. The common mechanism of trastuzumab resistance is that the selection of HER2 will not amplify clones ( Piro et al, 2018 ; Cavaliere et al, 2019 ). There are many mechanisms of primary or acquired resistance to anti-HER2 therapies, including impaired drug binding to HER2, constitutive activation of signaling pathways parallel or downstream of HER2, metabolic reprogramming or reduced immune system activation.…”
Section: Resistance In Targeted Therapymentioning
confidence: 99%